2021
DOI: 10.1002/pat.5457
|View full text |Cite
|
Sign up to set email alerts
|

Natural and synthetic functional materials for broad spectrum applications in antimicrobials, antivirals and cosmetics

Abstract: Antimicrobial resistance is the leading cause of burden on healthcare sector. There is scientific challenge of developing new functional material as a platform to prevent and treat viral and microbial infection and cosmetic utility. In material chemistry, there is progress in the development of functional material with advent of nanotechnology with aid of synthetic organic chemistry. The properties and application of material can be changed significantly by modification of the surface functional groups (namely… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 18 publications
(9 citation statements)
references
References 98 publications
0
4
0
Order By: Relevance
“…Heat treatment methods like blanching and novel techniques like ohmic heating are also utilized to suppress enzymatic activities that lead to spoilage [52]. Natural preservatives, such as essential oils from thyme and oregano, as well as antimicrobial peptides, have shown promise but face challenges in scalability and safety considerations [53]. Alao [2] reported that the most suitable condition for fresh fruits and vegetables in storage is the lowest temperature, which does not cause chilling injury to the fresh produce.…”
Section: Current and Emerging Technologies To Mitigate Deteriorationmentioning
confidence: 99%
“…Heat treatment methods like blanching and novel techniques like ohmic heating are also utilized to suppress enzymatic activities that lead to spoilage [52]. Natural preservatives, such as essential oils from thyme and oregano, as well as antimicrobial peptides, have shown promise but face challenges in scalability and safety considerations [53]. Alao [2] reported that the most suitable condition for fresh fruits and vegetables in storage is the lowest temperature, which does not cause chilling injury to the fresh produce.…”
Section: Current and Emerging Technologies To Mitigate Deteriorationmentioning
confidence: 99%
“…The remarkable structural features of amino adamantane and thiophene derivatives, which present exciting possibilities for biological uses, have aroused our interest in these compounds [1][2][3]. Amino adamantane derivatives have demonstrated effectiveness against a range of bacteria and fungi, making them promising candidates against infections [4][5][6].…”
Section: Introductionmentioning
confidence: 99%
“…Another study reported that Ga was able to inhibit the growth of Aspergillus fumigatus , a common cause of invasive aspergillosis in immuno­compromised patients . Beyond this, some studies suggest that GaLMs may also be effective against viral infections. , Overall, GaLMs have demonstrated significant potential for treating a broad range of microbial infections including those caused by eukaryotic pathogens such as fungi and viruses. Since GaLMs can interact with both prokaryotic and eukaryotic cells, it is important to fully understand the interactions between GaLMs and mammalian cells.…”
Section: Introductionmentioning
confidence: 99%